Does host plant drive variation in microbial gut communities in a recently shifted pest? - (:unkn) unknown (My University, 2019)
The recent shift of the indigenous longhorn beetle Cacosceles newmannii (Coleoptera: Cerambycidae) into sugarcane of KwaZulu-Natal has resulted in widespread concern surrounding its pest status and further potential for spread and damage in sugarcane crops. Although historically widespread in many biomes in southern Africa, C. newmannii is thought to thrive on indigenous forest trees, and no precise description of its biology is documented to date. Its shift into sugarcane was first recorded in 2015, and can possibly be attributed to several potential mechanisms, including abiotic and biotic factors. We hypothesized that the possible polyphagia of this species could cause, or result from, changes and modulations of the microbiome composition depending on the host. As a first step to test this hypothesis, we characterised whole body associated bacteria of C. newmannii larvae by high-throughput sequencing of a DNA amplicon coding for the 16S ribosomal RNA gene. Preliminary analyses were conducted on specimens fed with either peat or sugarcane, or both peat and sugarcane. Results showed that the diet seemed to influence the composition of the bacterialcommunity. In addition, a strong variability was observed among individuals fed on the same host. A larger batch of larvae were fed with either tea tree, eucalyptus, wattle or sugarcane for 7 weeks, and their growth rate was measured. Their microbiome composition will now be determined as described above. Analyses are in process and first results will be presented on this poster.
Keywords: African Research